Warm Water Strawberry Disease (WWSD) Outbreak in Cultured Rainbow Trout - Tanrıkul, TT; Dincturk, E; Şimşek, F (Journal of the Hellenic Veterinary Medical Society, 2025)
This study reports the first observation of warm-water strawberry disease in market-sized rainbow trout when the water temperature is above 15°C between April and September for 2 years in Turkey. Diseased fish with hemorrhagic inflammatory skin lesions were obtained from 4 different rainbow trout farms located in Muğla, Aegean Region of Turkey where the outbreak occurred. Microbiological, molecular, and histopathological analyze and scanning electron microscopy (SEM) examinations were performed to determine the causative agent of the disease, but no particular microbial growth and positive nested PCR results were obtained from the samples. In contrast, a rod-shaped coccoid bacterium was observed in SEM views of inflammatory skin samples. Intense lymphocytic infiltration was determined in both the epidermis and the dermis by histopathological examination. The etiology of this skin disease is still uncertain; however, the disease continues to spread in the region where most of the rainbow trout production occurs with economic loss in relation to inevaluable market size fish. It is important to observe the effects of the disease to prevent spread between farms and determine appropriate protection and control strategies.